Happiness-enhancing activities as a mediator between orientations to happiness and positive emotions: A longitudinal study - Ciupei Alina; Florean Ionuț Stelian; Stroian Paula (Acta Marisiensis - Seria Medica, 2025)
Objective: Although multiple studies have linked orientations to happiness to various well-being indicators, such as positive emotions, the underlying mechanisms of this relationship remain less understood. Given that orientations represent behavioral tendencies rather than concrete actions, this study aims to explore whether engaging in happiness-enhancing activities mediates their effect on positive emotions.